Downregulated MEG3 contributes to tumour progression and poor prognosis in oesophagal squamous cell carcinoma by interacting with miR-4261, downregulating DKK2 and activating the Wnt/β-catenin signalling - Ji Ma; Teng-Fei Li; Xin-Wei Han; Hui-Feng Yuan (Artificial Cells, Nanomedicine, and Biotechnology)
Long noncoding RNA (lncRNA) MEG3 has been widely reported to be decreased in a growing list of primary human tumours and play a key role in tumour suppression. However, there are few reports about MEG3 expression and function in oesophagal squamous cell carcinoma (ESCC). Here, we found that MEG3 expression was significantly downregulated in tumour tissues, and its low expression was associated with large tumour size, lymph node metastasis and advanced clinical stage in ESCC patients. Univariate and multivariate analyses revealed low expression of MEG3 as an independent predictor for disease-free survival and overall survival. Cell experiments showed that MEG3 inhibited ESCC cell proliferation, migration and invasion. Subsequently, miR-4261 was identified and confirmed to be the target of MEG3, and MEG3 functions, at least in part, by targeting miR-4261. Additionally, Dickkopf-2 (DKK2), a Wnt/β-catenin signalling inhibitor, was identified to be a target of miR-4261. MEG3 interacted with miR-4261, derepressed DKK2 and blocked the Wnt/β-catenin signalling, thereby inhibiting tumourigenesis and progression in ESCC. In vivo experiments also confirmed this conclusion. Our study for the first time elaborated the critical role of MEG3-miR-4261-DKK2-Wnt/β-catenin signalling axis in ESCC, and MEG3 could represent a novel diagnostic and prognostic biomarker and therapeutic target in ESCC.